Mode of action of a new nalidixic acid derivative, AB206. - Nagate, T (1980)
A new chemotherapeutic agent, AB206, shows potent antibacterial activity against gram-negative bacteria, including most of the nalidixic acid-resistant strains tested. It strongly inhibits deoxyribonucleic acid (DNA) synthesis in Escherichia coli, but only slightly inhibits ribonucleic acid and protein synthesis. Its activity on DNA synthesis in vivo and in vitro is greater than that of nalidixic acid. AB206 also strongly inhibits in vivo DNA synthesis in nalidixic acid-susceptible and -resistant clinical isolates of Proteus and Serratia. AB206 shows high penetrability into E. coli cells, as demonstrated by antibacterial activity with or without ethylenediaminetetraacetic acid, inhibition of in vivo and in vitro DNA synthesis, and uptake of the drug into cells, as compared to nalidixic acid. It appears that the high antibacterial activity of AB206 may be explained both by its potent inhibitory action against DNA synthesis and also by its high penetrability into bacterial cells.